Assessment of Tooth Movement and Bleeding on Probing: Clinical Indicators of Periodontal Disease Progression - Haleem, Riyam; Noor Musa; Hind Hadi (Indonesian Journal on Health Science and Medicine, 2025)
Periodontal disease is a chronic inflammatory condition that leads to the destruction of the supporting structures of the teeth. Two of its key clinical features are bleeding on probing (BOP) and tooth mobility, often reflective of underlying tissue breakdown. The aims of this study were to investigate the correlation between bleeding on probing and pathological tooth movement in patients with varying stages of periodontal disease, and to assess their diagnostic and prognostic significance. This cross-sectional study included 120 adult patients who underwent comprehensive periodontal examination. Parameters assessed included BOP, and tooth mobility. Statistical analysis was conducted to evaluate associations between BOP and pathological tooth movement. BOP was detected in 78.5% of patients, with a higher prevalence in the posterior sextants. Tooth mobility (Grade 2 or higher) was observed in 31.6% of the sample, predominantly in the maxillary and mandibular anterior teeth. A statistically significant correlation was found between BOP and pathological tooth movement (p < 0.01), with generalized BOP increasing the likelihood of tooth mobility by nearly fourfold (OR = 3.8). The presence of BOP is significantly associated with pathological tooth mobility, underlining its importance as a predictive marker in periodontal assessment. Early identification and intervention at sites with BOP may help prevent progressive tooth loss. Highlights: Iraqi Cardaria daraba L. contains alkaloids, flavonoids, tannins, terpenoids, and saponins with notable antioxidant activity (IC₅₀ = 2.96 mg/ml). HPLC analysis revealed high levels of vitamin C (42.8 mg/ml) and vitamin A (49.8 mg/ml) in the plant extract. AAS and FESEM-EDS analyses confirmed the presence of essential elements such as Fe, Zn, Ca, Mg, Se, and Sr, supporting its medicinal potential.